Mechanism of granuloma formation in sarcoidosis. Issue 1 (January 2017) - Sakthivel, Priya; Bruder, Dunja
Abstract : Purpose of review: The formation of noncaseating granuloma is a hallmark of pulmonary sarcoidosis. This review summarizes recent progress made to explain the cellular dynamics within the granuloma structure that may considerably differ between the two clinically distinct variants, that is, acute and chronic sarcoidosis. Recent findings: Compelling evidence exists that in acute but not chronic sarcoidosis CD4 + T lymphocytes specifically recognizing the auto-antigen vimentin on human leukocyte antigen-DR3 molecules accumulate in sarcoid granuloma. These so-called TH17.1 cells produce high amounts of the TH17 -related cytokines interleukin-17 (IL-17) and IL-22 in addition to interferon-γ. Moreover, regulatory T cells from patients with acute sarcoidosis are ICOS high, providing a mechanistic link to the comparably high concentration of IL-10 exclusively found in the airways of these patients. Next to obvious differences in T effector cell and Treg subsets, alveolar macrophages harbor a functional mitochondrial system in acute sarcoidosis patients, while this system is impaired in patients with chronic disease. Summary: We provide a comprehensive update on the cellular components and their functional implications in sarcoid granuloma formation, with special emphasis on the specific characteristics of granuloma in acute versus chronic sarcoidosis. Moreover, the specific antigens thought to be involved in both forms of the disease are discussed.